Securing SQL server : protecting your database from attackers - Cherry, Denny (Burlington, MA : Syngress, 2011)
'There is a lot at stake for administrators taking care of servers, since they house sensitive data like credit cards, social security numbers, medical records, and much more. In Securing SQL Server you will learn about the potential attack vectors that can be used to break into your SQL Server database, and how to protect yourself from these attacks. Written by a Microsoft SQL Server MVP, you will learn how to properly secure your database, from both internal and external threats. Best practices and specific tricks employed by the author will also be revealed. Learn expert techniques to protect your SQL database environment'--
Machine generated contents note: Chapter 1: Securing the Network Chapter 2: Database Encryption Chapter 3: SQL Password Security Chapter 4: Securing the Instance Chapter 5: Additional Security for an Internet Facing SQL Server and Application Chapter 6: SQL Injection Attacks Chapter 7: Database Backup Security Chapter 8: Auditing for Security Chapter 9: Server Rights Appendix A: External Audit Checklists .
Machine generated contents note: Chapter 1: Securing the Network Chapter 2: Database Encryption Chapter 3: SQL Password Security Chapter 4: Securing the Instance Chapter 5: Additional Security for an Internet Facing SQL Server and Application Chapter 6: SQL Injection Attacks Chapter 7: Database Backup Security Chapter 8: Auditing for Security Chapter 9: Server Rights Appendix A: External Audit Checklists .
Includes bibliographical references and index.
Keywords: SQL server; Client/server computing; Database security; Computer security